A balanced microbiota efficiently produces methane in a novel high-rate horizontal anaerobic reactor for the treatment of swine wastewater - Duda, Rose Maria [UNESP]; Vantini, Juliana da Silva [UNESP]; Martins, Larissa Scattolin [UNESP]; Varani, Alessandro de Mello [UNESP]; Franco Lemos, Manoel Victor; Tiraboschi Ferro, Maria Ines [UNESP]; Oliveira, Roberto Alves de [UNESP] (Elsevier B.V., 2015)
A novel combination of structurally simple, high-rate horizontal anaerobic reactors installed in series was used to treat swine wastewater. The reactors maintained stable pH, alkalinity, and volatile acid levels. Removed chemical oxygen demand (COD) represented 68% of the total, and the average specific methane production was 0.30 L CH4 (g removed CODtot) (1). In addition, next-generation sequencing and quantitative real-time PCR analyses were used to explore the methane-producing Archaea and microbial diversity. At least 94% of the sludge diversity belong to the Bacteria and Archaea, indicating a good balance of microorganisms. Among the Bacteria the Proteobacteria, Bacteroidetes and Firmicutes were the most prevalent phyla. Interestingly, up to 12% of the sludge diversity belongs to methane-producing orders, such as Methanosarcinales, Methanobacteriales and Methanomicrobiales. In summary, this system can efficiently produce methane and this is the first time that horizontal anaerobic reactors have been evaluated for the treatment of swine wastewater. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Biogas; Methanogenic archaea; Next generation sequencing; Quantitative real-time PCR; Renewable energy